Systematic review of literature: applications of molecular communications - Centeno-Romero, Maximiliano (2021)
Molecular communications constitute a dynamic research area that has a great potential to solve problems in disciplines as diverse as telecommunications engineering, nanotechnology, medicine, biotechnology and biochemistry. The study of this type of technology is recent and has given rise to a large number of publications that are scattered, and so, their study requires an effort to locate, organize and study them. This article presents a systematic literature review on molecular communications, in order to analyze how it is being applied in different fields. The study carried out contemplates the period between 2006 and 2018, and took into account 28 articles, after having passed through several filters and selection criteria. The result shows that the majority of published research works develop general aspects, but an important group addresses experimentation in the fields of health and biomedicine. The discussion of the results raises other possible uses of this type of communications and their possible integration with other technologies.